Cross-Sectional Survey of Physician-Reported Usage Patterns and GC–MS Phytochemical Profiling of Mahabala Tailam - Anoop A.K.; P. M. Varier; Ramesh P.R.; Haritha N.; Arjun M.K.; Deepak M.; Venugopalan P (Journal of Pharmaceutical Innovation, 2026)

Shifting ecological dynamics and biocoenosis of meiofauna in a changing Arctic fjord (Kongsfjorden, Svalbard) - P.P. Krishnapriya; Anoop N. Nair; N.K. Aswathy; K.B. Kavya; P.C. Shamily Catherine; Suhaana M. Nazar; S. Bijoy Nandan; M. Harikrishnan; A.V. Shibu (Polar Biology, 2026)

Retraction Note: Potential innovation against Alzheimer’s disorder: a tricomponent combination of natural antioxidants (vitamin E, quercetin, and basil oil) and the development of its intranasal delivery - Chenmala Karthika; Anoop Pattanoor Appu; Rokeya Akter; Md.Habibur Rahman; Priti Tagde; Ghulam Md. Ashraf; Mohamed M. Abdel-Daim; Syed Shams ul Hassan; Areha Abid; Simona Bungau (Environmental Science and Pollution Research, 2026)

Spatial Factors Shape Taxonomic and Functional Beta‐Diversity in Water‐Filled Tree Holes in Different Biogeographical Regions - Francesca Cerroti; Thibaut Rota; Francisco Valente‐Neto; K. T. Fahis; Red Calore; Gustavo Q. Romero; Karumampoyil Sakthidas Anoop Das; Andreas Bruder; Martin M. Gossner (Ecology Letters, 2025)
A central goal in ecology is to understand the mechanisms shaping community assembly at different spatial and temporal scales. This knowledge is crucial for improving conservation strategies, but remains limited for ephemeral habitats. We investigated the contribution of environmental, that is, physical and chemical microhabitat properties, and spatial factors in shaping taxonomic and functional β‐diversity of macroinvertebrate metacommunities inhabiting water‐filled tree holes (WTHs) in forests in three biogeographical regions: Temperate‐Mediterranean (France), Neotropical (Brazil), and Palaeotropical (India). We conducted standardised surveys of 35 WTHs per region on 100 ha plots. Spatial factors had a stronger effect on taxonomic and functional β‐diversity than environmental properties. Species richness differences dominated taxonomic β‐diversity. Processes driving functional β‐diversity showed biogeographic patterns, with functional turnover being pronounced in the Palaeotropical rainforest. These findings highlight the key role of spatial processes in shaping WTH metacommunities and emphasise the need for conservation strategies that maintain habitat connectivity and old‐growth forests.

Preliminary analysis and applications of the Indian Ocean wave drifter program - P. G. Remya; N. Suresh Kumar; Sundhar B. Mithun; B. Praveen Kumar; T. R. Anoop; Venkat Shesu Reddem; C. Jeyakumar; Aneesh A. Lotliker; E. Pattabhi Rama Rao; T. M. Balakrishnan Nair (Frontiers in Marine Science, 2025)
The Southern Ocean (SO) is a critical driver of global wave dynamics, generating long-period swells that propagate vast distances and significantly impact far distant coastal regions, including the Indian coastal regions. Climate change has intensified westerly winds and altered storm tracks in the Southern Hemisphere, resulting in higher wave heights and longer periods, which in turn increase the risk to coastal regions.​ However, the remote and harsh environment in the SO has historically limited in-situ wave observations, hindering a comprehensive understanding of the wave characteristics in the region. To bridge this gap, the Indian National Centre for Ocean Information Services (INCOIS) launched the Indian Ocean Wave Drifter (IOWD) program in 2021 under the Deep Ocean Mission to address the in-situ data gap in the Southern Indian Ocean. Through the deployment of GPS-enabled directional wave spectra drifters, the program has enabled near-real-time observations of wave characteristics across the SO. This article highlights the early outcomes of the IOWD program, including wave model validation, Stokes drift estimation, and swell tracking. The study emphasizes the importance of sustained in-situ observations from remote oceans for improving wave forecasting, enhancing coastal preparedness, and advancing scientific understanding of wave–current interactions and climate variability in the Indian Ocean region.

Bioactive human platelet lysate gel for enhanced proliferation of human umbilical cord tissue derived mesenchymal stem cells - Seetha S. Babu; M. Kamaraj; T. G. Nithya; P. Raghu Babu; Gayathri Anoop (Cell and Tissue Banking, 2025)

Intensification of pastoralism ∼ 8 ka: Non-pollen palynomorphs analyses from the Rawatsera palaeolake sediments profile, Central Himalaya, India - Mohammad Firoze Quamar; Nagendra Prasad; Maneesha M. ET; Paulramasamy Morthekai; Anoop K. Singh; Lalit M. Joshi; Bahadur S. Kotlia; Dhruv Sen Singh; Mohammad Javed (Review of Palaeobotany and Palynology, 2025)

Exploring machine learning models to predict atmospheric water harvesting with an ion deposition membrane - Giulio Barletta; Shashwata Moitra; Sybil Derrible; Alex Mathew; Anoop Muraleedharan Nair; Constantine M. Megaridis (Journal of Water Process Engineering, 2025)

Lyophilization of dehydrated human amniotic membrane: a proactive approach to preserve growth factors for enhanced wound healing - Gayathri Anoop; M. Kamaraj; T. G. Nithya; Pothireddy Raghu Babu; Seetha S. Babu (Cell and Tissue Banking, 2025)

Analysis of Human Activities, Built-Up and Rainfall Impacts on Groundwater Potential Zones Using GIS and AHP Techniques: A Case of Karaman River, Southern Western Ghats, India - B. Upendra; K. Nanda; K. Jesuraja; M. Ciba; G. Sreenivasulu; K. Anoop Krishnan (Water Conservation Science and Engineering, 2024)

One-pot synthesis of stable vitamin C analogue using trans-glycosylating enzyme from Aspergillus carbonarius BTCF 5 - Reshma M. Mathew; Meena Sankar; Athiraraj Sreeja-Raju; Prajeesh Kooloth-Valappil; Anoop Puthiyamadam; Dileep Raveendran-Nair; Rajeev K. Sukumaran (Biocatalysis and Agricultural Biotechnology, 2024)

Inflammation and aging-related disease: A transdisciplinary inflammaging framework - Brian J. Andonian; Joseph A. Hippensteel; Katrina Abuabara; Eileen M. Boyle; James F. Colbert; Michael J. Devinney; Adam S. Faye; Bharati Kochar; Jiha Lee; Rachel Litke; Devika Nair; Sebastian E. Sattui; et al. (GeroScience, 2024)

Toxicity and biokinetics following pulmonary exposure to aluminium (aluminum): A review - Niels Hadrup; Jorid B. Sørli; Bjørn M. Jenssen; Ulla Vogel; Anoop K. Sharma (Toxicology, 2024)

The mafic–ultramafic roots of a Mesoarchean microblock in southern India: Insights from petrochemistry and isotope geochronology of the Coorg Block - Cheng-Xue Yang; M. Santosh; Pin Gao; Y. Anilkumar; K.S. Anoop; Sung Won Kim; Sanghoon Kwon (Precambrian Research, 2024)

Feeding potential and foraging behaviour of cheilomenes sexmaculata (F.) on cotton whitefly, Bemisia tabaci (Gennadius) - Rakesh Kumar; Sachin S. Suroshe; Y. Venkanna; M. C. Keerthi; Anoop Kumar; Subhash Chander (International Journal of Tropical Insect Science, 2024)

A layered gabbro-anorthosite suite from Attappadi: Chemical and isotopic signature of Neoarchean subduction tectonics in the Southern Granulite Terrane, India - K.V. Kavyanjali; Y. Anilkumar; M. Santosh; Cheng-Xue Yang; K.S. Anoop; Anjana Mathew; Sanghoon Kwon (Lithos, 2024)

Microcystin influence on soil-plant microbiota: Unraveling microbiota modulations and assembly processes in the rhizosphere of Vicia faba - El Mahdi Redouane; Andrés Núñez; Wafa Achouak; Mohamed Barakat; Anoop Alex; José Carlos Martins; Zakaria Tazart; Richard Mugani; Soukaina El Amrani Zerrifi; Mohammed Haida; Ana M. García; Alexandre Campos; et al. (Science of The Total Environment, 2024)

Synthesis and characterization of gold nanoparticles using Brevibacterium casei (SOSIST-06) isolated from Southern Ocean water samples and their in vitro and in silico anti-WSSV activity - R. Namitha; B. Abirami; B.S. Anoop; D.V. Diya Dominic; Ahna Ameer; K. Manigundan; M. Radhakrishnan; P. Santhiya; Parli V. Bhaskar; K. Govindaraju; I.S. Bright Singh; G. Dharani (Aquaculture, 2024)

Unravelling submarine channel morphology in the lower Bengal Fan through ultra-high-resolution autonomous underwater vehicle (AUV) survey - C. M. Bijesh; S. Vadakkepuliyambatta; J. John Savio; S. Ramesh; N. R. Ramesh; T. R. Anoop; P. Kunnummal; R. Ramesh; P. John Kurian; G. A. Ramadass (Geo-Marine Letters, 2023)

The Coorg Block, southern India: Insights from felsic and mafic magmatic suites on Mesoarchean plate tectonics and correlation with supercontinent Ur - Cheng-Xue Yang; M. Santosh; Jarred C. Lloyd; Stijn Glorie; Pin Gao; Bing Yu; Y. Anilkumar; K.S. Anoop; Sung-Won Kim (Gondwana Research, 2023)

Estimation of soil moisture and soil temperature over India using the Noah multi-parameterisation land surface model - Noel M. Chawang; Sai Krishna V. S. Sakuru; Anoop Sampelli; Srinivasulu Jella; Kusuma G. Rao; M. V. Ramana (Modeling Earth Systems and Environment, 2023)

Pattern and drivers of danaine butterfly migration in Southern India: implications for conservation - P. A. Vinayan; M. A. Yathumon; N. S. Sujin; B. N. Anjan Kumar; P. A. Ajayan; P. K. Muneer; N. M. Vishnu; C. S. Anwar; N. R. Anoop (Journal of Insect Conservation, 2023)

Comparison of the solid-state and submerged fermentation derived secretomes of hyper-cellulolytic Penicillium janthinellum NCIM 1366 reveals the changes responsible for differences in hydrolytic performance - Meena Sankar; Reshma M Mathew; Anoop Puthiyamadam; Athiraraj Sreeja-Raju; Meera Christopher; Digambar Vitthal Gokhale; Rajeev K. Sukumaran (Bioresource Technology, 2023)

Lipid-Based Vesicles: a Non-invasive Tool for Transdermal Drug Delivery - Alan Raj; Sarath Chandran C.; Anoop Narayanan V.; Aparna Ivon; Nazeera Farzana N. M.; Neethu Narayan P. P. (Journal of Pharmaceutical Innovation, 2022)

An environmental green approach for the effective removal of malachite green from estuarine waters using Pistacia vera L. shell-based active carbon - Harsha Mahadevan; P. V. M. Nimina; K. Anoop Krishnan (Sustainable Water Resources Management, 2022)

RETRACTED ARTICLE: Potential innovation against Alzheimer’s disorder: a tricomponent combination of natural antioxidants (vitamin E, quercetin, and basil oil) and the development of its intranasal delivery - Chenmala Karthika; Anoop Pattanoor Appu; Rokeya Akter; Md. Habibur Rahman; Priti Tagde; Ghulam Md. Ashraf; Mohamed M. Abdel-Daim; Syed Shams ul Hassan; Areha Abid; Simona Bungau (Environmental Science and Pollution Research, 2022)

Composition and distribution pattern of plankton communities in lagoon and offshore region of Kavaratti Atoll, Lakshadweep Archipelago, India - Sibin Antony; Vinu V. Dev; M. Ratheesh Kumar; K. Anoop Krishnan (Sustainable Water Resources Management, 2021)

Grazing behaviour of tropical calanoid copepods and its effect on phytoplankton community structure - M Ratheesh Kumar; K Anoop Krishnan (Environmental Monitoring and Assessment, 2021)

Capsule Network–based architectures for the segmentation of sub-retinal serous fluid in optical coherence tomography images of central serous chorioretinopathy - S. J. Pawan; Rahul Sankar; Anubhav Jain; Mahir Jain; D. V. Darshan; B. N. Anoop; Abhishek R. Kothari; M. Venkatesan; Jeny Rajan (Medical & Biological Engineering & Computing, 2021)

Monitoring of heavy metal contamination in Netravati river basin: overview of pollution indices and risk assessment - S. Gayathri; K. Anoop Krishnan; A. Krishnakumar; T. M. Vishnu Maya; Vinu V. Dev; Sibin Antony; V. Arun (Sustainable Water Resources Management, 2021)

Chemical carcinogen safety testing: OECD expert group international consensus on the development of an integrated approach for the testing and assessment of chemical non-genotoxic carcinogens - Miriam N. Jacobs; Annamaria Colacci; Raffaella Corvi; Monica Vaccari; M. Cecilia Aguila; Marco Corvaro; Nathalie Delrue; Daniel Desaulniers; Norman Ertych; Abigail Jacobs; Mirjam Luijten; Federica Madia; et al. (Archives of Toxicology, 2020)
While regulatory requirements for carcinogenicity testing of chemicals vary according to product sector and regulatory jurisdiction, the standard approach starts with a battery of genotoxicity tests (which include mutagenicity assays). If any of the in vivo genotoxicity tests are positive, a lifetime rodent cancer bioassay may be requested, but under most chemical regulations (except plant protection, biocides, pharmaceuticals), this is rare. The decision to conduct further testing based on genotoxicity test outcomes creates a regulatory gap for the identification of non-genotoxic carcinogens (NGTxC). With the objective of addressing this gap, in 2016, the Organization of Economic Cooperation and Development (OECD) established an expert group to develop an integrated approach to the testing and assessment (IATA) of NGTxC. Through that work, a definition of NGTxC in a regulatory context was agreed. Using the adverse outcome pathway (AOP) concept, various cancer models were developed, and overarching mechanisms and modes of action were identified. After further refining and structuring with respect to the common hallmarks of cancer and knowing that NGTxC act through a large variety of specific mechanisms, with cell proliferation commonly being a unifying element, it became evident that a panel of tests covering multiple biological traits will be needed to populate the IATA. Consequently, in addition to literature and database investigation, the OECD opened a call for relevant assays in 2018 to receive suggestions. Here, we report on the definition of NGTxC, on the development of the overarching NGTxC IATA, and on the development of ranking parameters to evaluate the assays. Ultimately the intent is to select the best scoring assays for integration in an NGTxC IATA to better identify carcinogens and reduce public health hazards.

Spatial variation in morphology of the White-browed Laughingthrush (Garrulax sannio) and its relationship with climate conditions in southern China - Longying Wen; Janine M. Antalffy; Kevin Messenger; Wei Zhao; Fangqing Liu; Fasheng Zou; Karumampoyil Sakthidas Anoop Das; Yong Wang (Journal of Ornithology, 2020)

On the generation and propagation of Makran swells in the Arabian Sea - Thondithala R. Anoop; Puthuveetil R. Shanas; Valliyil M. Aboobacker; V. Sanil Kumar; Leela Sheela Nair; Ravindran Prasad; Srinivas Reji (International Journal of Climatology, 2020)
Persistent and periodic northerly low‐level jets have been identified in the South Asian mid‐latitudes and subtropics, which are modified by the presence of Makran mountain ranges adjacent to the central south coast of Pakistan, where they blow predominantly in the west‐northwest to northeast directions. These winds lead to the generation of a new wave system and propagate through the Arabian Sea as “makran swells”. They are prevalent during October to May. The measurements along the west coast of India reveal systematic variations in the wave spectra relating the makran events. This has been further verified through the WaveWatch III simulations forced by the CFSR winds. The significant wave heights up to 4.5 m were hindcasted in the northern Arabian Sea during these events. Once generated, the makran swells propagate to the eastern Arabian Sea and western Arabian Sea with directional sectors of 300–360° and 0–60°, respectively. The characteristic features and the spatial extension of the makran swells are particularly analysed.

A porcine-cholecyst-derived scaffold for treating full thickness lacerated skin wounds in dogs - Satheesan Karthika; Sainulabdeen Anoop; C. B. Devanand; M. K. Narayanan; Madhavan Unni; Saji Eassow; Thapasimuthu Anilkumar (Veterinary Research Communications, 2018)

Denitrification rates in estuarine sediments of Ashtamudi, Kerala, India - Junaid Hassan Salahudeen; R. R. Reshmi; K. Anoop Krishnan; M. S. Ragi; Salom Gnana Thanga Vincent (Environmental Monitoring and Assessment, 2018)

Reconstruction of Indian monsoon precipitation variability between 4.0 and 1.6 ka BP using speleothem δ18O records from the Central Lesser Himalaya, India - Lalit M. Joshi; Bahadur Singh Kotlia; S. M. Ahmad; C.-C. Wu; Jaishri Sanwal; Waseem Raza; Anoop K. Singh; C.-C. Shen; Tengwen Long; Arun K. Sharma (Arabian Journal of Geosciences, 2017)

Indian Ocean Dipole modulated wave climate of eastern Arabian Sea - T. R. Anoop; V. Sanil Kumar; P. R. Shanas; J. Glejin; M. M. Amrutha (Ocean Science, 2016)
Intrinsic modes of variability have a significant role in driving the climatic oscillations in the oceanic processes. In this paper, we investigate the influence of an inter-annual mode of variability, the Indian Ocean Dipole (IOD), on the wave climate of the eastern Arabian Sea (AS). Using measured, modeled and reanalysis wave data and reanalysis wind data, we show that the IOD plays a major role in the variability of wave climate of the study region. Due to the IOD-induced changes in equatorial sea surface temperature and sea level pressure, the winds from the northern AS gets modified and cause inter-annual variability in the wave climate over the eastern AS. The changes in wind field over the AS due to the IOD influence the generation or dissipation of the wave field and hence cause a decrease in northwest short-period waves during positive IOD and an increase during negative IOD.

Effect of growth rate on wood quality of teak (Tectona grandis L. f.): a comparative study of teak grown under differing site quality conditions - M. C. Anish; E. V. Anoop; R. Vishnu; B. Sreejith; C. M. Jijeesh (Journal of the Indian Academy of Wood Science, 2015)

Complete genome sequencing and evolutionary analysis of dengue virus serotype 1 isolates from an outbreak in Kerala, South India - M. Anoop; Ashish J. Mathew; B. Jayakumar; Aneesh Issac; Sajith Nair; Rachy Abraham; M. G. Anupriya; E. Sreekumar (Virus Genes, 2012)

Rainfall Estimation from Combined Observations Using KALPANA-IR and TRMM- Precipitation Radar Measurements over Indian Region - Anoop Kumar Mishra; Rakesh M. Gairola; Vijay K. Agarwal (Journal of the Indian Society of Remote Sensing, 2012)

Provenance variation in wood chemical properties of Acacia mangium willd. and Acacia auriculiformis cunn., grown in a wet humid site in Thrissur district of Kerala, South India - K. M. Mohammed Raphy; E. V. Anoop; P. Aruna; V. V. Sheena; V. Ajayghosh (Journal of the Indian Academy of Wood Science, 2011)

Cholesterol ester transfer protein and apolipoprotein E gene polymorphisms in hyperlipidemic Asian Indians in North India - Kiran Meena; Anoop Misra; Naval Vikram; Shakir Ali; R. M. Pandey; Kalpana Luthra (Molecular and Cellular Biochemistry, 2011)

DOAS observations of formaldehyde and its impact on the HOx balance in the tropical Atlantic marine boundary layer - Anoop S. Mahajan; Lisa K. Whalley; Elena Kozlova; Hilke Oetjen; Luis Mendez; Kate L. Furneaux; Andrew Goddard; Dwayne E. Heard; John M. C. Plane; Alfonso Saiz-Lopez (Journal of Atmospheric Chemistry, 2010)

Genetic characterization of 2006–2008 isolates of Chikungunya virus from Kerala, South India, by whole genome sequence analysis - E. Sreekumar; Aneesh Issac; Sajith Nair; Ramkumar Hariharan; M. B. Janki; D. S. Arathy; R. Regu; Thomas Mathew; M. Anoop; K. P. Niyas; M. R. Pillai (Virus Genes, 2010)

Dimethyl sulfoxide toxicity kinetics in intact articular cartilage - Heidi Y. Elmoazzen; Anoop Poovadan; Garson K. Law; Janet A. W. Elliott; Locksley E. McGann; Nadr M. Jomha (Cell and Tissue Banking, 2007)

Apolipoprotein E polymorphism in Northern Indian patients with coronary heart disease: Phenotype distribution and relation to serum lipids and lipoproteins - Kalpana Luthra; Balram Bharghav; Shivani Chabbra; Nibhriti Das; Anoop Misra; Dharam P. Agarwal; Ravindra M. Pandey; L.M. Srivastava (Molecular and Cellular Biochemistry, 2002)